Method for recycling positive electrode material of waste NCM lithium ion battery
By using GUC-TA synthesized by guanidine hydrochloride and tartaric acid as DES, combined with calcination and oil bath heating and stirring technology, the recycling process of the used NCM lithium-ion battery cathode material is simplified, solving the problems of complex processes and high costs in the existing technology, and achieving efficient separation and regeneration of Li, Ni, Co, Mn.
Patent Information
- Application Number
- CN202510136594.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the process of recycling waste LIB positive electrode materials using DES is complicated, costly, time-consuming and difficult to regenerate waste LIB.
GUC-TA synthesized by guanidine hydrochloride and tartaric acid is used as DES, and the used NCM lithium-ion battery positive electrode material powder is mixed with DES by calcining and heating and stirring in an oil bath, and ethanol is added to produce crystallization, so as to achieve separation of Li and Ni, Co, and Mn. Then Li is recovered by evaporation and carbonization treatment, and the precursor is mixed and Li2CO3 is sintered to obtain a regenerated NCM lithium-ion battery positive electrode material.
The recycling process of the positive electrode material of waste NCM lithium-ion batteries is simplified, which reduces cost, shortens time consumption, and improves the recovery rate of DES, achieving efficient separation and regeneration of Li, Ni, Co, and Mn.
Smart Images

Figure CN119650930A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste battery recycling, and in particular to a method for recycling positive electrode materials of waste NCM lithium-ion batteries. Background Art
[0002] Lithium-ion batteries (LIB) are widely used in new energy vehicles and various electronic products, but the effective use time of LIB is usually only 3 to 5 years, which means that a large number of lithium-ion batteries will face the problem of retirement. The content of precious metals lithium, nickel, cobalt and manganese in the positive electrode materials of waste nickel cobalt manganese oxide lithium-ion batteries (waste NCM lithium-ion batteries) is higher than that in the original ore. Reasonable recycling of metals in the positive electrode materials of waste NCM lithium-ion batteries can not only "turn waste into treasure", but also avoid threats to human health.
[0003] For the recovery of valuable metals in waste LIB positive electrode materials, the following recovery technologies are currently widely used: 1) Pyrometallurgy. This process is simple and efficient. It removes organic binders in electrode materials by high-temperature incineration, and at the same time causes metals and their compounds therein to undergo oxidation-reduction reactions, and recovers low-boiling-point metals and their compounds in the form of condensation. However, this method consumes a lot of energy and is costly, and the organic matter in lithium-ion batteries will produce a large amount of harmful gases under high temperature conditions; 2) Hydrometallurgy. This method uses chemical reagents to dissolve the positive electrode materials in waste LIBs and separate the valuable metals in the leaching solution. It has the advantages of large processing capacity, high leaching efficiency, and lower energy consumption, but the leaching process will produce a large amount of acidic or alkaline wastewater, and is prone to produce toxic gases such as Cl2 and NOx, causing secondary pollution.
[0004] Deep Eutectic Solvents (DES) are a type of ionic liquid, composed of hydrogen bond acceptors (HBA) and hydrogen bond donors (HBD). The eutectic point of the mixture is lower than the melting point of any pure component, and it has the advantages of good solubility, environmental friendliness, low cost, and low volatility. Since DES has good solubility for metals and metal oxides, it can be used as a substitute for inorganic acid leaching of waste LIBs. Therefore, in recent years, a variety of deep eutectic solvents have been used to recycle waste LIB cathode materials.
[0005] At present, in the research on the recovery of metals from waste LIB positive electrode materials by low eutectic solvents, most of the studies only discussed the leaching of valuable metals in positive electrode materials, and a few studies discussed the selective separation and purification of metals after leaching of positive electrode materials. The recovery steps of these studies are mainly divided into two parts: the leaching of valuable metals in positive electrode materials and the separation of valuable metals in leachate. Extraction and chemical precipitation are commonly used methods for selective separation and purification of valuable metals. For example, in the related technology, when choline chloride-lactic acid DES was used to recover LiNiCoO2, it was found that after adding 16g / L DES at 105°C for 5h, the leaching rates of Li, Ni, and Co could all reach 100%; then oxalic acid was added to the leachate as a precipitant, and Ni and Co were separated from the leachate in the form of oxalate at 40°C, and then sintered at high temperature to obtain nickel cobalt oxide as a precursor material for standby use; and the remaining Li in the leachate was recovered in the form of lithium metaphosphate by adding phosphoric acid, and finally nickel cobalt manganese oxide and lithium metaphosphate were mixed in proportion and sintered at high temperature to obtain regenerated positive electrode materials.
[0006] From the perspective of leaching conditions, the leaching conditions of existing DES are relatively harsh (high temperature and long time), which is not conducive to widespread application in actual work; in addition, the existing DES leaching positive electrode materials after the separation and recovery of metals in the leachate is relatively complicated. Whether it is extraction or chemical precipitation, not only does it require the additional addition of relatively expensive chemical reagents, but it also requires a complex process to achieve the separation of the target metals. In addition, the addition of additional chemical reagents makes DES regeneration difficult, which increases the cost of raw material use.
[0007] Therefore, providing a method for recycling waste NCM lithium-ion battery positive electrode materials with a simple process and easy DES recovery has become a technical problem that needs to be urgently solved by those skilled in the art. Summary of the invention
[0008] The invention discloses a method for recycling waste NCM lithium-ion battery positive electrode materials, so as to solve the technical problems of using DES to recycle waste LIB positive electrode materials in the related art, such as complex process, high cost, long time consumption and difficulty in DES regeneration.
[0009] In order to solve the above problems, the present invention adopts the following technical solutions: The method for recycling waste NCM lithium-ion battery positive electrode materials of the present invention comprises the following steps: The positive electrode sheets of the waste NCM lithium-ion batteries are calcined, and the positive electrode material powder is collected and sieved for later use; The cathode material powder is mixed with DES, heated and stirred in an oil bath, ethanol is added, and after crystallization, solid-liquid separation is performed to obtain a Li-containing supernatant and a tartrate precipitate containing Ni, Co, and Mn, and the DES is GUC-TA synthesized using guanidine hydrochloride and tartaric acid as raw materials; The Li supernatant is evaporated and concentrated and then carbonized to obtain Li2CO3; Using tartrate precipitates containing Ni, Co and Mn as precursors, the precursors are mixed with Li2CO3 and ground, and then sintered at high temperature to obtain regenerated NCM lithium-ion battery positive electrode materials.
[0010] According to an optional embodiment, when the precursor is mixed with Li2CO3, the amount of Li2CO3 added satisfies the molar ratio of Li:Ni:Co:Mn of 1:0.5:0.2:0.3; The precursor and Li2CO3 were sintered at 500℃ for 4h, and then the temperature was raised to 800℃ for 15h. After cooling to room temperature, LiNi 0.5 Co 0.2 Mn 0.3 O2 positive electrode material powder.
[0011] According to an optional embodiment, the GUC-TA is prepared by: Guanidine hydrochloride and tartaric acid were mixed in a molar ratio of 1:1, deionized water was added, and stirred at 80°C until a uniform transparent solution was obtained, and then cooled to room temperature and stored for later use; The amount of deionized water added is 30% of the sum of the weight of guanidine hydrochloride and tartaric acid.
[0012] According to an optional embodiment, when the positive electrode material powder is mixed with DES, the solid-liquid ratio of the mixed solution is 20-70 g / L; The obtained mixed solution is reacted at 60-110° C. and a stirring speed of 700 rpm for 30-150 min to obtain a Li-containing supernatant and a tartrate precipitate containing Ni, Co, and Mn.
[0013] According to an optional embodiment, the positive electrode material powder and DES are heated and stirred in an oil bath, and after the solution is cooled, ethanol is added to the solution as an anti-solvent, and the reaction is carried out at room temperature and a stirring speed of 400 rpm for 0 to 96 hours, and the product after the reaction is centrifuged to obtain a crystalline solid and a supernatant; The crystalline solid is a tartrate precipitate containing Ni, Co and Mn.
[0014] According to an optional embodiment, the amount of ethanol added is 2 to 25 times the volume of the DES.
[0015] According to an optional embodiment, the centrifugal separation to obtain the crystalline solid and the supernatant further comprises the following steps: The crystalline solid was dried at 80 °C for 6 h, the ethanol was removed, and it was cooled to room temperature before use; placing the supernatant in a distillation apparatus to recover ethanol at 95° C. and obtain regenerated ethanol; The residual liquid obtained after recovering the ethanol was dried at 80°C for 12 h to remove the ethanol and obtain the regenerated GUC-TA.
[0016] According to an optional embodiment, when the positive electrode material powder is mixed with DES, the DES is GUC-TA synthesized using guanidine hydrochloride and tartaric acid as raw materials; or the DES is regenerated GUC-TA; When ethanol is added to the Li-containing supernatant, the ethanol is fresh ethanol or regenerated ethanol.
[0017] According to an optional embodiment, the regenerated GUC-TA is mixed with the positive electrode material powder, heated and stirred in an oil bath, and after adding ethanol, the supernatant is separated and the lithium in the supernatant is recovered and carbonized to obtain Li2CO3.
[0018] According to an optional embodiment, the lithium in the supernatant is recovered and carbonized to obtain Li2CO3, which comprises the following steps: The supernatant was dried at 80°C for 24 h to obtain a concentrated mixed metal solution; The mixed metal solution was mixed with an ammonia solution and a NaOH solution, and the pH of the system was maintained at 11 to remove impurities, and the mixture was aged for 12 hours at a stirring speed of 700 rpm to obtain a mixed solution; The mixed solution is filtered to obtain a Li-enriched solution and a precipitate containing Ni, Co, and Mn impurities; The Li-enriched liquid was evaporated and concentrated again, and a saturated Na2CO3 solution was added at a stirring speed of 700 rpm and a temperature of 95°C. After reacting for 30 minutes, the slurry was filtered while hot, and the precipitate was washed with boiling water several times. The filter cake was dried to obtain Li2CO3.
[0019] The technical solution adopted by the present invention can achieve the following beneficial effects: In the first aspect, the present invention discloses a method for recovering positive electrode materials of waste NCM lithium-ion batteries. GUC-TA synthesized from guanidine hydrochloride and tartaric acid is used as DES to leach valuable metals from positive electrode materials of waste NCM lithium-ion batteries, thereby obtaining a Li-containing supernatant and a tartrate precipitate containing Ni, Co, and Mn. That is, the present invention can achieve the separation of Li from Ni, Co, and Mn in one step. Compared with the prior art method of leaching Li, Ni, Co, and Mn into a solution and then separating Li from Ni, Co, and Mn by extraction or co-precipitation, the method of the present invention can shorten the recovery process of positive electrode materials of waste NCM lithium-ion batteries.
[0020] In the second aspect, the method for recovering waste NCM lithium-ion battery positive electrode materials of the present invention uses DES to leach the valuable metals of the waste NCM lithium-ion battery positive electrode materials, and then further enhances the separation effect of Li from Ni, Co, and Mn by adding ethanol anti-solvent crystallization. The ratio of Ni, Co, and Mn in the obtained solid material satisfies 5:2:3, so the solid material can be directly used as a precursor to obtain regenerated NCM lithium-ion battery positive electrode materials without the need to additionally add Ni, Co, and Mn.
[0021] In the third aspect, the method for recovering the positive electrode materials of waste NCM lithium-ion batteries of the present invention uses GUC-TA synthesized from guanidine hydrochloride and tartaric acid as DES to leach the valuable metals in the positive electrode materials of waste NCM lithium-ion batteries, and can achieve valuable metal leaching under mild conditions (temperature 90°C, time 90 min).
[0022] Fourthly, in the method for recycling positive electrode materials of waste NCM lithium-ion batteries of the present invention, GUC-TA synthesized with guanidine hydrochloride and tartaric acid as raw materials is a green solvent, and both GUC-TA and ethanol can be recycled and reused. The recovery rate of GUC-TA synthesized with guanidine hydrochloride and tartaric acid as raw materials reaches 80%, and the recovery rate of ethanol reaches 91.6%, which can effectively reduce the recycling cost of positive electrode materials of waste NCM lithium-ion batteries.
[0023] It can be seen that the method for recycling waste NCM lithium-ion battery positive electrode materials of the present invention can solve the technical problems of using DES to recycle waste LIB positive electrode materials in the related art, such as complex process, high cost, long time consumption and difficult DES regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a flow chart of a method for recycling waste NCM lithium-ion battery positive electrode materials according to an embodiment of the present application; Figure 2 This is a test result diagram of the effect of different reaction temperatures on the transfer rate of each metal in the embodiment of the present application; Figure 3 1 is a graph showing the test results of the effects of different solid-liquid ratios on the transfer rates of various metals in the embodiments of the present application; Figure 4 This is a test result diagram of the effect of different reaction times on the transfer rate of each metal in the embodiment of the present application; Figure 5 This is a test result diagram of the effect of different crystallization times on Li crystallization rate in the embodiment of the present application; Figure 6 This is a test result diagram of the effect of different crystallization times on the crystallization rates of Ni, Co, and Mn in the examples of the present application; Figure 7 This is a test result diagram of the effect of different ethanol addition amounts on Li crystallization rate in the examples of the present application; Figure 8 This is a test result diagram of the effect of different ethanol addition amounts on the crystallization rates of Ni, Co, and Mn in the examples of the present application; Fig. 9 is the XRD pattern of the anti-solvent crystal product obtained in the examples of the present application; Fig.10 is the infrared spectrum of RDES and DES obtained in the examples of the present application; Fig.11 is the infrared spectrum of REG and commercial ethanol obtained in the examples of the present application; Fig.12 This is a comparison chart of metal recovery rates of ethanol recovered in the embodiment of the present application and commercial ethanol; Fig.13 This is the XRD spectrum of Li2CO3 recovered in the embodiment of the present application; Fig.14 This is the XRD spectrum of the regenerated positive electrode material obtained in the example of the present application. DETAILED DESCRIPTION
[0026] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0027] The terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.
[0028] In the related art of using DES to recycle waste LIB positive electrode materials, Li, Ni, Co, and Mn in the waste LIB positive electrode materials are all in the leachate. In order to separate Li from Ni, Co, and Mn, other substances need to be added to the leachate for extraction or co-precipitation. That is, in the related art of using DES to recycle waste LIB positive electrode materials, at least two steps are required to separate Li from Ni, Co, and Mn.
[0029] The present application utilizes guanidine hydrochloride and tartaric acid to recycle waste LIB positive electrode materials, which can achieve the main enrichment of Li in the solution when the positive electrode material is leached, while Co, Ni, and Mn mainly exist in the form of precipitation. The separation of Li from Ni, Co, and Mn can be achieved in one step, which can shorten the recovery process. The present application also further enhances the separation effect of Li from Ni, Co, and Mn by adding ethanol anti-solvent crystallization, and the obtained solid can be directly used as a precursor without the need to add additional Ni, Co, and Mn, which can further shorten the recovery process and reduce costs.
[0030] The following is combined with Figures 1 to 14 , the method for recycling waste NCM lithium-ion battery positive electrode materials provided in this application is described in detail.
[0031] Figure 1 The flowchart of the method for recycling positive electrode materials of waste NCM lithium-ion batteries in this embodiment is shown. The method for recycling positive electrode materials of waste NCM lithium-ion batteries in this embodiment comprises the following steps: Step 1: Obtaining NCM lithium-ion battery positive electrode materials.
[0032] Place the waste NCM lithium-ion battery in a 10g / L NaCl solution for discharge treatment, and air dry naturally after the discharge is completed. After air drying, manually disassemble to obtain the positive electrode, negative electrode, diaphragm and metal shell of the waste NCM lithium-ion battery. Calcine the disassembled positive electrode sheet in a muffle furnace at 300℃ for 1h to remove impurities such as binder and electrolyte. After calcination, take out and separate the positive electrode material powder from the surface of the aluminum foil with a brush, pass through a 200-mesh sieve, and obtain a relatively pure waste NCM lithium-ion battery positive electrode material powder, which is stored for later use.
[0033] Step 2: Preparation of DES.
[0034] Weigh guanidine hydrochloride (GUC) and tartaric acid (TA) in a molar ratio of 1:1 and slowly add them into a round-bottom flask, add deionized water, the weight of which is 30wt% of the sum of the weight of guanidine hydrochloride and tartaric acid, add a magnetic stirrer, stir at 80°C until a uniform and transparent solution is obtained, cool to room temperature and store for later use. During the heating process, plug the bottle mouth tightly to prevent GUC-TA from absorbing too much moisture in the air.
[0035] Step 3: Leaching of valuable metals from waste NCM lithium-ion battery cathode materials.
[0036] Step 3-1: Investigate the effect of reaction temperature on metal transfer rate.
[0037] 0.1 g of waste NCM lithium-ion battery cathode material powder was added to six 30 ml culture bottles, GUC-TA was added at a solid-liquid ratio of 50 g / L, and a magnetic stirring rotor was added before sealing. The sealed culture bottles were placed in a constant temperature oil bath and heated to 60°C, 70°C, 80°C, 90°C, 100°C, and 110°C, respectively, and reacted for 90 min at a stirring speed of 700 rpm to leach out the valuable metals (Li, Co, Mn, Ni) in the waste NCM lithium-ion battery cathode material. After the leaching, a large amount of pink precipitate was present in the leachate. After solid-liquid separation, the content of each metal in the supernatant and the pink precipitate was measured. The ratio of the content of Li, Ni, Co, and Mn in the supernatant to the total content in the cathode material was measured by formula (1), that is, the transfer rate of the metal to the solution (when it is not necessary to measure the content of each metal in the supernatant and the pink precipitate, there is no need to perform the separation step, and the anti-solvent crystallization of step 4 can be directly performed after the leachate is cooled).
[0038] (1) Where: η i is the transfer rate of the ith metal (Li, Ni, Co, Mn) to the solution, %; C i is the concentration of the ith metal in the leachate, g / L; V is the volume of the leachate, L; m is the mass of the NCM powder, g; w iis the mass proportion of the ith metal in the NCM lithium-ion battery positive electrode material, %.
[0039] The results are as follows Figure 2 As shown. At 60°C, the transfer rates of Li, Ni, Co, and Mn are 69.65%, 42.61%, 44.67%, and 42.08%, respectively. When the temperature rises to 90°C, the transfer rates of Li, Ni, Co, and Mn are 97.84%, 8.11%, 6.04%, and 20.54%, respectively. As the reaction temperature increases, the transfer rate of Li gradually increases, while that of Ni, Co, and Mn decreases on the contrary. When the temperature continues to rise to 110°C, the transfer rates of Li, Ni, Co, and Mn are 98.75%, 8.87%, 8.72%, and 20.43%, respectively. There is no significant change in the transfer rate of each metal element. Therefore, 90°C is a suitable reaction temperature from the perspective of energy saving while ensuring that Li and Ni, Co, and Mn can be well separated.
[0040] Step 3-2: Investigate the effect of solid-liquid ratio on metal transfer rate.
[0041] 0.1 g of waste NCM lithium-ion battery cathode material powder was added to each of the six 30 ml culture bottles, and GUC-TA (GUC-TA can be freshly prepared in step 2 or recycled in step 5. The one used here is freshly prepared in step 2) was added to each bottle at a solid-liquid ratio of 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, and 70 g / L, respectively. Then, a magnetic stirring rotor was added and sealed. The sealed culture bottle was placed in a constant temperature oil bath and heated to 90 ° C. The reaction was carried out at a stirring speed of 700 rpm for 90 minutes to leach the valuable metals (Li, Co, Mn, Ni) in the waste NCM lithium-ion battery cathode material. After the leaching was completed, a large amount of pink precipitate existed in the leachate. After solid-liquid separation, the metal content in the supernatant and the pink precipitate was measured, and the transfer rate of Li, Ni, Co, and Mn to the solution was measured by formula (1).
[0042] The results are as follows Figure 3As shown. When the solid-liquid ratio is 70g / L, the transfer rates of Li, Ni, Co, and Mn are 93.62%, 7.67%, 4.52%, and 13.83%, respectively. When the solid-liquid ratio is 20g / L, the transfer rates of Li, Ni, Co, and Mn increase to 98.43%, 36.08%, 12.02%, and 60.07%, respectively. This shows that when the dosage of the positive electrode material powder remains unchanged, as the dosage of the GUC-TA solution increases, the transfer rate of Li increases, and more Ni, Co, and Mn are transferred from the precipitate to the solution. When the solid-liquid ratio is 50g / L, the transfer rate of Li is as high as 97.79%, and only 7.16%, 5.33%, and 19.99% of Ni, Co, and Mn exist in the solution, which can achieve the purpose of separating Li and Ni, Co, and Mn. Therefore, considering the economic cost, a solid-liquid ratio of 50g / L is a suitable reaction solid-liquid ratio.
[0043] Step 3-3: Investigate the effect of reaction time on metal transfer rate.
[0044] 0.1g of waste NCM lithium-ion battery cathode material powder was added to each of the six 30ml culture bottles, GUC-TA was added at a solid-liquid ratio of 50g / L, and a magnetic stirring rotor was added before sealing. The sealed culture bottles were placed in a constant temperature oil bath and heated to 90°C. Under a stirring speed of 700rpm, each culture bottle was reacted for 30min, 60min, 90min, 120min, and 150min to leach the valuable metals (Li, Co, Mn, Ni) in the waste NCM lithium-ion battery cathode material. After the leaching was completed, a large amount of pink precipitate existed in the leachate. After solid-liquid separation, the metal contents in the supernatant and the pink precipitate were measured, and the transfer rates of Li, Ni, Co, and Mn to the solution were measured by formula (1).
[0045] The results are as follows Figure 4 As shown. When the reaction time is 30 minutes, the transfer rates of Li, Ni, Co, and Mn are 88.66%, 23.02%, 17.44%, and 30.57%, respectively; as the reaction time increases to 90 minutes, the transfer rate of Li increases to 97.96%, and the transfer rates of Ni, Co, and Mn decrease to 6.62%, 5.69%, and 19.14%, respectively; when the reaction time continues to extend to 150 minutes, the transfer rates of each metal are basically stable. It shows that as the reaction time increases, when the concentration of Ni, Co, and Mn leached from the positive electrode material increases to a sufficient concentration, they will form insoluble complexes with tartaric acid (TA). When the reaction time is 90 minutes, the positive electrode material of the NCM lithium-ion battery is completely dissolved, the separation of Li and Ni, Co, and Mn reaches the optimal state, and it can also save time cost, so 90 minutes is selected as the optimal reaction time.
[0046] Therefore, the optimal reaction conditions for the leaching of valuable metals in the cathode material of waste NCM lithium-ion batteries are: reaction temperature 90°C, solid-liquid ratio S / L=50g / L, and reaction time 90min. Under the optimal reaction conditions, 97.79%, 7.16%, 5.33%, and 19.99% of Li, Ni, Co, and Mn in the cathode material are present in the supernatant, respectively.
[0047] The element content of the pink precipitate obtained under the conditions was tested, and the results showed that the mass fraction of Li in the pink precipitate obtained under the optimal leaching conditions was 0.02%, and the mass fractions of Ni, Co, and Mn were 13.37%, 6.07%, and 7.15%, respectively. This indicates that when the NCM lithium-ion battery cathode material is leached in GUC-TA, most of the Li is present in the leachate, while most of the Ni, Co, and Mn are present in the pink precipitate, and the separation of Li from Ni, Co, and Mn has been basically successfully achieved.
[0048] Step 4: Antisolvent Crystallization.
[0049] After dissolving the NCM lithium-ion battery cathode material, GUC-TA can initially separate Li from Ni, Co, and Mn, but the separation is not complete, especially for Mn. The ratio of Ni, Co, and Mn in the precipitate needs to be adjusted before it can be used as a cathode material precursor. In this embodiment, ethanol is used as an anti-solvent to further recover the metal, which can further enhance the separation effect of Li from Ni, Co, and Mn. The ratio of Ni, Co, and Mn in the obtained precipitate satisfies 5:2:3, and it can be used as a cathode material precursor without the need to add additional Ni, Co, and Mn.
[0050] Step 4-1: Investigate the effect of stirring contact time on metal crystallization rate.
[0051] After the leaching reaction is completed and the solution is cooled (no filtration step is required after the leaching reaction is completed here), 25 times the volume of GUC-TA ethanol (ethanol can be fresh ethanol or recovered in step 5. The ethanol used here is fresh ethanol) is added as an anti-solvent to seven strain bottles containing waste NCM lithium-ion battery positive electrode material leachate, and a magnetic stirrer is added. After sealing, it is placed on a magnetic stirrer and reacted at 400 rpm and room temperature for 0 h, 2 h, 18 h, 24 h, 48 h, 72 h, and 96 h respectively; the reaction product is centrifuged to obtain a crystalline solid and a supernatant. The supernatant is tested for metal content, and the crystallization rate of Li, Ni, Co, and Mn is calculated by formula (2).
[0052] (2) Where: γ i is the crystallization rate of the ith metal (Li, Ni, Co, Mn), %; Ci is the concentration of the ith metal in the supernatant, g / L; V1 is the volume of DES added, L; V2 is the volume of ethanol added, L; m is the mass of NCM powder, g; w i is the mass proportion of the ith metal in the NCM lithium-ion battery positive electrode material, %.
[0053] The results are as follows Figure 5 and Figure 6 As shown. Figure 5 It can be seen that with the increase of crystallization time, the crystallization rate of Li increased from 10.39% to 32.19% at 18h, and then remained stable; when the crystallization time exceeded 48h, the crystallization rate of Li continued to increase, reaching 42.42% at 96h. Figure 6 It can be found that the crystallization rates of Ni, Co, and Mn show a trend of rising first and then maintaining stability. After stirring for 18 hours, the crystallization rates of Ni, Co, and Mn increased from 99.78%, 99.90%, and 99.17% to 100%, 99.96%, and 99.68%, respectively. After more than 18 hours, the crystallization rates of Ni and Co are basically stable, and the crystallization rate of Mn slightly decreases to 99.58% and then basically stabilizes. In summary, although the crystallization rate of Li did not reach the highest at 18 hours, the crystallization rates of Ni, Co, and Mn all exceeded 99.5%, and the purpose of the present invention is to recover Ni, Co, and Mn to obtain NCM lithium-ion battery positive electrode material precursor materials. Therefore, from the perspective of saving time cost, 18 hours is a suitable anti-solvent crystallization time.
[0054] Step 4-2: Effect of the ratio of ethanol to leaching solution on the metal crystallization rate.
[0055] After the leaching reaction is completed and the solution is cooled, ethanol with a volume of 2, 4, 6, 8, 12, 16, and 25 times the volume of GUC-TA is added as an anti-solvent to each of the strain bottles containing the waste NCM lithium-ion battery positive electrode material leachate, and a magnetic stirrer is added. After sealing, it is placed on a magnetic stirrer and reacted at 400 rpm and room temperature for 18 hours; the product after the reaction is centrifuged to obtain a crystalline solid and a supernatant. The metal content of the supernatant is tested, and the crystallization rate of Li, Ni, Co, and Mn is calculated by formula (2).
[0056] The results are as follows Figure 7 and Figure 8 As shown. Figure 7 It can be seen that when the volume ratio of ethanol to leaching solution is 2, the crystallization rate of Li is 50.26%. When the volume ratio of ethanol to leaching solution increases to 12, the crystallization rate of Li increases to 67.64%, and then begins to decline. When the volume ratio of ethanol to leaching solution reaches 25, the crystallization rate of Li is only 32.20%, indicating that adding too little or too much ethanol is not conducive to the crystallization of Li. Figure 8 It can be seen that with the increase of ethanol addition, the crystallization rates of Ni, Co and Mn show an overall upward trend. When the volume ratio of ethanol to leachate increases from 2 to 4, the crystallization rates of Ni, Co and Mn increase from 94.29%, 98.19% and 81.16% to 96.41%, 99.54% and 89.41%, respectively; when the volume ratio of ethanol to leachate is greater than 4, the crystallization rate of Co tends to be stable, while Ni and Mn continue to rise. When the volume ratio of ethanol to leachate reaches 25, the crystallization rates of Ni, Co and Mn are as high as 99.98%, 100% and 99.58%, respectively; therefore, the amount of ethanol addition has the least effect on the crystallization rate of Co and the greatest effect on the crystallization rate of Mn.
[0057] When the volume ratio of ethanol to leachate is 12, the crystallization rates of Li, Ni, Co, and Mn are 67.64%, 98.57%, 100%, and 97.24%, respectively. At this time, the crystallization rate of Li is the highest, and the crystallization rates of Ni, Co, and Mn have all exceeded 97%. While ensuring the high crystallization rates of Ni, Co, and Mn, the higher the crystallization rate of Li, the more beneficial it is to the synthesis of NCM lithium-ion battery positive electrode materials, and the less Li content in DES, which is beneficial to the reuse of DES. In addition, the more ethanol is added, the higher the economic cost. Therefore, after comprehensive consideration, 12 times the volume of GUC-TA ethanol is selected as the appropriate amount of anti-solvent added.
[0058] Therefore, under the optimal crystallization conditions (reaction time = 18h, Vethanol: Vleaching solution = 12), the crystallization rates of Li, Ni, Co, and Mn were 67.64%, 98.57%, 100%, and 97.24%, respectively. This result proves that the addition of ethanol can enhance the precipitation effect of metal ions.
[0059] In addition, the antisolvent crystalline solid was subjected to XRD detection, and the test results are as follows: Fig. 9 As shown. XRD results show that the diffraction peaks of the antisolvent crystallized solid are basically consistent with those of the standard cards PDF#01-0230, PDF#22-1672, PDF#01-0321, and PDF#33-0910, indicating that the antisolvent crystallized product is a tartaric acid metal salt. The metal element content of the antisolvent crystallized product was detected, and the test results showed that Li∶Ni∶Co∶Mn=0.59∶0.5∶0.21∶0.32 in the antisolvent crystallized product, among which Ni∶Co∶Mn is close to 5∶2∶3, indicating that the product can be used as a precursor material for synthesizing positive electrode materials.
[0060] Step 5: Recovery of DES and ethanol.
[0061] After the anti-solvent crystallization, the supernatant obtained by centrifugation is a mixed solution containing Li, GUC-TA and ethanol. The mixed solution is placed in a round-bottom flask and a magnetic stirring rotor is added, placed in a distillation apparatus, and regenerated ethanol (REG) is recovered at 95°C. After the distillation, the residual liquid obtained in the round-bottom flask is dried at 80°C for 12 hours to remove excess ethanol, which is the regenerated GUC-TA (referred to as RDES). When ethanol is separated from the solution, the regenerated RDES is light yellow, which is caused by the residual metal ions. The residual amounts of Li, Ni, Co, and Mn in RDES were measured to be 0.3597 mg / ml, 0.0507 mg / ml, 0.0046 mg / ml, and 0.0982 mg / ml, respectively.
[0062] DES and RDES were analyzed by FTIR. Fig.10 .from Fig.10 From the infrared spectrum, RDES and DES have the same characteristic peaks, among which the peak at 1723cm -1 and 1664cm -1 The characteristic peak at 1130cm is the stretching vibration of C=O; -1 and 1080cm -1 The two characteristic peaks are the stretching vibration of CO, proving that the structure of the recovered RDES is consistent with that of DES. Fig.10 It can also be seen that there is still residual ethanol in the RDES that has not been completely separated.
[0063] The regenerated RDES was used again to leach the positive electrode material of NCM lithium-ion battery under the optimal leaching conditions (T=90℃, S / L=50g / L, Time=90min) to explore the recycling performance of RDES. After RDES leached the positive electrode material, the contents of Li, Ni, Co, and Mn in the leaching solution were measured. The transfer rates of Li, Ni, Co, and Mn to the solution when RDES was used to leach the positive electrode material were calculated by formula (3) to be 94.87%, 12.32%, 25.40%, and 33.37%, respectively. This proves that RDES still has good leaching ability.
[0064] (3) Where: η RDESi is the transfer rate of the ith metal (Li, Ni, Co, Mn) into RDES, %; C i is the concentration of the ith metal in the leaching solution, g / L; n i is the residual amount of the i-th metal in RDES, g / L; V is the volume of RDES, L; m is the mass of NCM powder, g; w i is the mass proportion of the ith metal in the NCM positive electrode material, %.
[0065] After the ethanol was successfully separated from the DES, the metal content of the recovered ethanol REG was tested. The test results showed that only a very small amount (0.0002 mg / ml) of Li existed in REG, indicating that it was of high purity. The FTIR spectra of the recovered ethanol and commercial ethanol were compared and analyzed. The results are as follows: Fig.11 Compared with commercial ethanol, the recovered ethanol has a -1 Except for a faint peak, the characteristic peaks of OH, CH, and CO are basically consistent with those of commercial ethanol.
[0066] Under the optimal leaching conditions (T = 90 ° C, S / L = 50g / L, Time = 90min), REG and commercial ethanol were used for anti-solvent crystallization, and the recovery results of Li, Ni, Co, and Mn were as follows: Fig.12 As shown. Fig.12 It can be seen that the recovery rates of Li, Ni, Co, and Mn by REG and commercial ethanol are basically the same.
[0067] The structures of RDES and REG separated and recovered by distillation were basically unchanged compared with fresh DES and ethanol, and they were capable of secondary utilization, indicating that the recovery method of DES and ethanol was feasible.
[0068] Step 6: Recovery of Li.
[0069] After using RDES to leach waste NCM lithium-ion battery cathode materials, the RDES obtained again is enriched with a large amount of Li and a small amount of Ni, Co, and Mn, and its leaching capacity decreases. Therefore, when using RDES to leach waste NCM lithium-ion battery cathode materials, the supernatant obtained by anti-solvent crystallization can be concentrated to obtain a mixed metal solution to facilitate the recovery of Li therein. The number of DES cycles is 1 to 3 times.
[0070] Specifically, there is a large amount of Li and a small amount of Ni, Co, and Mn in the supernatant. The supernatant is dried at 80°C for 24 hours to obtain a concentrated mixed metal solution. A flask is used as a reaction container, 0.5M ammonia solution and a magnetic stirrer are added to the flask, heated to 55°C in a constant temperature magnetic stirrer, and 4M NaOH, 2M ammonia solution and a mixed metal solution are slowly added. The pH of the reaction solution is always maintained at 11 during the whole process, and the speed is fixed at 700rpm. After the feeding is completed, it is aged for 12 hours, and a small amount of nickel and manganese-containing precipitates generated in the process are filtered to obtain a Li-enriched solution. The obtained Li-enriched solution is evaporated and concentrated again, and a saturated Na2CO3 solution is slowly added at 700rpm in a 95°C environment. After reacting for 30 minutes, the slurry is filtered while hot, and the precipitate is washed with boiling water several times. The filter cake is placed in an oven to dry to obtain Li2CO3.
[0071] The recovered Li2CO3 was analyzed by XRD, and the results are as follows Fig.13 The recovered Li2CO3 is a white powder, and its diffraction peaks are consistent with the characteristic peaks of the Li2CO3 standard card (PDF#87-0728) and the peaks are sharp, without other impurity diffraction peaks, indicating that the recovered Li2CO3 has a high purity.
[0072] Step 7: Regeneration of positive electrode material.
[0073] Determine the mass fraction and molar ratio of Li, Ni, Co, and Mn in the precursor material; add a certain amount of Li2CO3 according to the content of Ni, Co, and Mn in the precursor material (so that the molar ratio of Li: Ni: Co: Mn is 1: 0.5: 0.2: 0.3, Li2CO3 can be recovered in step 6 or freshly prepared), mix and grind thoroughly, and then perform two-stage sintering. First, sinter at 500°C for 4h to fully fuse the added Li2CO3 with the precursor material, and then raise the temperature to 800°C for sintering for 15h. During this process, the heating and cooling rates are both 5°C / min. After the muffle furnace is cooled to room temperature, the regenerated positive electrode material is obtained, and XRD test is performed on it. The test results are as follows: Fig.14 shown.
[0074] from Fig.14 It can be seen that the diffraction peaks of the regenerated positive electrode material correspond one by one to the diffraction peaks of the standard card PDF#09-0063 of LiNiO2, without other impurity peaks. The peaks at the (006), (012), (018) and (110) positions show obvious splitting, indicating that the regenerated synthesized lithium nickel cobalt manganese oxide has good crystallinity and has a hexagonal α-NaFeO2 structure of R3m.
[0075] Table 1 shows the unit cell parameters of the regenerated positive electrode material, where the c / a value is an important indicator for measuring the layered structure of the ternary material. When the ratio exceeds 4.9, it is generally considered that the material has formed a layered structure; and as the c / a value further increases, the layered order also increases. After calculation, the c / a value of the regenerated positive electrode material in this embodiment is 4.931, indicating that the synthesized positive electrode material has a good layered structure. In layered transition metal oxide positive electrode materials, R=I(006)+I(012)) / I(101) is often used to measure the hexagonal layered order of the material to determine whether there is a more serious cation mixing in the layered structure. Generally speaking, it is better when the R value is around 0.5, and the smaller the R value, the better the hexagonal layered order. After calculation, the R value of the regenerated positive electrode material in this embodiment is 0.45, proving that its cation order is high.
[0076] It can be seen that the method of this embodiment can regenerate and synthesize positive electrode materials with good layered structures.
[0077] Table 1 Unit cell parameters of regenerated cathode materials
[0078] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0079] In addition, it should be noted that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in a reverse order according to the functions involved. For example, the described methods may be performed in an order different from that described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.
[0080] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for recycling waste NCM lithium-ion battery positive electrode materials, characterized in that: The steps include: The positive electrode sheets of the waste NCM lithium-ion batteries are calcined, and the positive electrode material powder is collected and sieved for later use; The cathode material powder is mixed with DES, heated and stirred in an oil bath, ethanol is added, and after crystallization, solid-liquid separation is performed to obtain a Li-containing supernatant and a tartrate precipitate containing Ni, Co, and Mn, and the DES is GUC-TA synthesized using guanidine hydrochloride and tartaric acid as raw materials; The Li supernatant is evaporated and concentrated and then carbonized to obtain Li2CO3; Using tartrate precipitates containing Ni, Co and Mn as precursors, the precursors are mixed with Li2CO3 and ground, and then sintered at high temperature to obtain regenerated NCM lithium-ion battery positive electrode materials.
2. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 1, characterized in that: When the precursor is mixed with Li2CO3, the amount of Li2CO3 added satisfies the molar ratio of Li∶Ni∶Co∶Mn of 1∶0.5∶0.2∶0.3; The precursor and Li2CO3 were sintered at 500℃ for 4h, then the temperature was raised to 800℃ for 15h, and after cooling to room temperature, LiNi 0.5 Co 0.2 Mn 0.3 O2 positive electrode material powder.
3. The method for recovering waste NCM lithium-ion battery positive electrode materials according to claim 1 or 2, characterized in that: The GUC-TA was prepared by the following method: Guanidine hydrochloride and tartaric acid were mixed in a molar ratio of 1:1, deionized water was added, and stirred at 80°C until a uniform transparent solution was obtained, and then cooled to room temperature and stored for later use; The amount of deionized water added is 30% of the sum of the weight of guanidine hydrochloride and tartaric acid.
4. The method for recovering waste NCM lithium-ion battery positive electrode materials according to claim 1 or 2, characterized in that: When the cathode material powder is mixed with DES, the solid-liquid ratio of the mixed solution is 20~70g / L; The obtained mixed solution is reacted at 60-110° C. and a stirring speed of 700 rpm for 30-150 min to obtain a Li-containing supernatant and a tartrate precipitate containing Ni, Co, and Mn.
5. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 4, characterized in that: The cathode material powder and DES were heated and stirred in an oil bath. After the solution was cooled, ethanol was added to the solution as an anti-solvent. The reaction was carried out at room temperature and a stirring speed of 400 rpm for 0 to 96 hours. The product after the reaction was separated by centrifugation to obtain a crystalline solid and a supernatant. The crystalline solid is a tartrate precipitate containing Ni, Co and Mn.
6. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 5, characterized in that: The amount of ethanol added is 2 to 25 times the volume of the DES.
7. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 5, characterized in that: The centrifugal separation obtains a crystalline solid and a supernatant, and further comprises the following steps: The crystalline solid was dried at 80 °C for 6 h, the ethanol was removed, and it was cooled to room temperature before use; placing the supernatant in a distillation apparatus to recover ethanol at 95° C. and obtain regenerated ethanol; The residual liquid obtained after recovering the ethanol was dried at 80°C for 12 h to remove the ethanol and obtain the regenerated GUC-TA.
8. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 7, characterized in that: When the positive electrode material powder is mixed with DES, the DES is GUC-TA synthesized using guanidine hydrochloride and tartaric acid as raw materials; or the DES is regenerated GUC-TA; When ethanol is added to the Li-containing supernatant, the ethanol is fresh ethanol or regenerated ethanol.
9. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 7, characterized in that: The regenerated GUC-TA is mixed with the positive electrode material powder, heated and stirred in an oil bath, and ethanol is added, followed by separation to obtain a supernatant, and the lithium in the supernatant is recovered and carbonized to obtain Li2CO3.
10. The method for recycling waste NCM lithium-ion battery positive electrode materials according to claim 9, characterized in that: The lithium in the supernatant is recovered and carbonized to obtain Li2CO3, which comprises the following steps: The supernatant was dried at 80°C for 24 h to obtain a concentrated mixed metal solution; The mixed metal solution was mixed with an ammonia solution and a NaOH solution, and the pH of the system was maintained at 11 to remove impurities, and the mixture was aged for 12 hours at a stirring speed of 700 rpm to obtain a mixed solution; The mixed solution is filtered to obtain a Li-enriched solution and a precipitate containing Ni, Co, and Mn impurities; The Li-enriched liquid was evaporated and concentrated again, and a saturated Na2CO3 solution was added at a stirring speed of 700 rpm and a temperature of 95°C. After reacting for 30 minutes, the slurry was filtered while hot, and the precipitate was washed with boiling water several times. The filter cake was dried to obtain Li2CO3.
Citation Information
Patent Citations
Method for recovering valuable metal from waste and old nickel cobalt lithium manganate ternary battery positive materials
CN107994288A
Method for recycling nickel-cobalt-manganese-lithium from waste power lithium ion battery black powder
CN111519031A
Method for recovering valuable metals from positive electrode material of waste ternary lithium battery
CN112646974A
Method for recycling lithium carbonate through scrapped lithium ion batteries
CN117747996A
Method for preparing of ion-exchange type nano-lithiummanganese oxide powder adsorbent by gel process
KR1020050045786A